The effect of a rational-emotional counseling program on developing emotional empathy among university students (Journal of the College of Basic Education, 2022)
The aim of the research is to know the effect of a rational-emotional counseling program on developing emotional empathy among university students. M of both sexes (males - females), as the original research community amounted to (120) male and female students, and the sample of the experiment was distributed as follows:1- Applying the emotional empathy scale to the research sample of the fourth stage students, which numbered (120) male and female students.2- The researcher chose the students who got less than the hypothetical mean of the scale, which amounted to (120) degrees on the emotional empathy scale, and their number was (70) male and female students.3- (10) male and female students were excluded because they did not have enough desire to participate in the experiment.Distribution of (60) male and female students randomly into two groups of (30) male and female students in the experimental group, and (30) male and female students in the control group. In order to reach the results of the research, the researcher used a set of (statistical methods, including: The following statistical methods were used to process the research data, and this was done through the Statistical Package for Social Sciences (SPSS).Chi-square: To find out the significance of the differences in expert opinions on the validity of a scale.The t-test for two independent samples: to extract the discriminatory power of the items of the emotional empathy scale, and to identify the differences between the experimental and control groups in the post test.Pearson's correlation coefficient: to calculate the relationship of the paragraph's degree with the total degree, the relationship of the paragraph with the domain, and the relationship of the domains with each other for the measure of emotional empathy, and to verify the stability by the method of the split-half test.